Strategic Measures to Curb Insecurity Problems Affecting Students - Ologele, Ibrahim; Fatimah, Ibrahim (Pedagogia: Jurnal Ilmiah Pendidikan, 2023)
Insecurity is the state of being subject to danger or injury. The study investigated strategic measures to curb insecurity problem affecting students. The study adopted descriptive research design of survey type.  The study population comprised of all undergraduates in the study area. Multi-stage sampling technique was used to select two hundred and forty-nine respondents participated in the study. A researcher structured questionnaire which was validated and tested for reliability was adopted for the study. A coefficient of 0.79 was obtained using Split-half method. The instrument was administered by the researchers and three trained research assistants. Inferential statistics of chi-square was used to analysed the  hypotheses postulated for this study at 0.05 alpha level. The findings of this study revealed that, emergency alarm significantly curb insecurity affecting students because the calculated chi-square value of 448.67  greater than the table value of 16.92 @ 0.05 alpha level, self-defense skills significantly curb insecurity affecting students because the calculated  chi-square value of 290.28  greater than the table value of 16.92 @ 0.05 alpha level. The study concluded that placing of emergency alarm at designated school areas suppress insecurity and self-defense skills plays a vital role in ensuring safety of students. The researchers recommends among others that the school authority should procure and placed emergency alarm at designated areas in the school premises to serve as means of alert students against insecurity problems affecting students in the school which will  also scare away miscreants from committing their wicked activities.